Final Assessment of the Strategic Approaches to Community Safety Initiative (SACSI) in New Haven, Connecticut, 1994-2001 - Hartstone, Eliot C. ([Verlag nicht ermittelbar], 2006)
This study was conducted to assess the effectiveness of New Haven, Connecticut's Strategic Approaches to Community Safety Initiative (SACSI) project, named TimeZup, by measuring the impact of the program on public safety, public fear, and law enforcement relationships and operations. The study was conducted using data retrieved from the New Haven Police Department's computerized records and logs, on-site questionnaires, and phone interviews. Important variables included in the study are number of violent gun crimes committed, number and type of guns seized by the police, calls to the police involving shootings or gun shots, the date and time of such incidents, residents' perception of crime, safety and quality of life in New Haven, and supervisees' perceptions of the TimeZup program.